The Effects of Individual and Group Behavior on Employee Performance Mediated by Occupational Safety and Health (OSH) at PT. Andalan Permata Buana - Al Ucok, Imran (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to determine and explain the effect of individual behavior and group behavior on employee performance mediated by Occupational Safety and Health (OSH) at PT Andalan Permata Buana. This study uses quantitative data. The study population amounted to 202 people, and the sample taken was 132 people. Data analysis used the PLS Structural Equational Modeling (SEM) statistical test. Data analysis techniques include path diagrams and measurement model evaluation (construct validity evaluation, reliability evaluation, goodness of fit model, hypothesis testing, indirect effect testing, conversion of path diagrams into structural models, and dominant influence). The results of this study are as follows: 1) Individual behavior has a positive and significant effect on employee performance 2) individual behavior has a positive and significant effect on employee performance through occupational safety and health. 3) group behavior has a positive and significant effect on employee performance. 4) group behavior has a positive and significant effect on employee performance through occupational safety and health. 5) occupational safety and health have a positive and significant effect on employee performance. 6) individual behavior has a positive and significant effect on occupational safety and health. 7) group behavior has a positive and significant effect on occupational safety and health. This research is relevant for PT. Andalan Permata Buana in identifying effective strategies to improve employee performance through individual behavior management, group dynamics, and OSH program implementation. This is important to create a safe and productive work environment.